Decennial comparison of changes in social vulnerability: a municipal analysis in support of risk management - Tavares, A.O. (2018)
The concept of Social Vulnerability (SV) is characterized and distinguished by its complexity and multidisciplinarity. This concept takes into account the specific characteristics of the individual and his social and economic relations, as well as the physical environment where he is inserted. These differentiating characteristics make Social Vulnerability (SV) an indispensable work tool in the process of characterizing and understanding the degree of exposure of communities, as well as evaluating their capacity for resilience and recovery from hazardous events. This paper presents a comparison between the SV performed in 2008 with the results obtained in 2017 for the 278 municipalities of mainland Portugal. The methodology was based on the work developed by the Center for Social Studies of the University of Coimbra, which is distinguished by the fact that SV is composed of two components: Criticity and Support Capability. The analysis of SV and its components was done using Principal Components Analysis (PCA) starting from an initial set of 235 variables (90 for Criticality and 145 for Support Capability). With respect to Criticality, the results point out the importance of factors related to the economic condition, employment and factors related to the disadvantaged population and risk groups. Support Capability is strongly influenced by the population density and the most relevant factors for the final results are those related to civil protection response, economic and environmental dynamism and logistic and service capacity. Regarding the SV spatial distribution, the highest values are located mainly in the central and northern parts of the country, with emphasis on the Douro river valley and surrounding municipalities; also a general decrease of SV was recorded in the southern regions from 2008 to 2017.